La Charte de la langue française et la langue du travail - Garant, Louis (Les Cahiers de droit, 1982)
The 1977 « Charte de la langue française » can only be considered as a major event in the history of the French language in Quebec. The law enacting the Charter states, in its first section, that French is the official language in Quebec. Consequently, French is the language of work in Quebec. The « Office de la langue française », therein instituted, is empowered to see that fact and law be but one in such field. The following pages will be concerned mainly with the interpretation of the various sections of the Charter relative to the language of work, interpretation which will envisage the possible jurisdictional conflicts as well as take into account the consequences of the application of the Charter in labour relations.